n → ∞ lim ( n sin n π ) ( 1 + n π ) n
The limit above has a closed form. Find the value of this closed form.
If this limit can be approximated as 3 . 1 9 × 1 0 η , where η is an integer , find η .
You may use a calculator for the final step of your calculation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thanks for the solution! That's an interesting calculation.
Log in to reply
Did the same way, but wanted to ask what should be the condition that we split the limit of the exponent and base?
Log in to reply
What do you think the condition is? Figure it out and write a note for the community to learn from!
After the first equation, you can just directly replace the right hand side with exp(pi) * ln(pi). This follows from compound definition of exp function and the famous limit sin(x)/x. It's simpler that way.
I got answer (π^e)^π but answer doesn't match with that value.
Could you explain the standard limits used?
Or the easiest we can do is to find the limit of (1+Π\n)^n separately that comes to be e^Π. And then the evaluation of (n[sin{Π\n}]) which comes to be Π . and after taking out limits of both the function we can combine our result and get Π^e^Π
Taking the natural log on both sides -
ln ( L ) = lim n → ∞ ( 1 + n π ) n ⋅ ( n sin n π ) = e π lim n → ∞ ln ( n sin n π )
Let lim n → ∞ ln ( n sin n π ) = L 1 . Using L'Hopital's
⇒ e L 1 = n → ∞ lim n 1 sin ( n π ) = n → ∞ lim n 2 − 1 n 2 − π ⋅ cos ( n π ) = π ⋅ n → ∞ lim cos ( n π ) = π
⇒ L 1 = ln ( π )
Therefore
L = e e π ⋅ ln ( π ) = π e π ≈ 3 . 1 9 × 1 0 1 1
| The limits are both finite in the division!
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Limits by Logarithms
Let the limit be y , then
ln y ln ( ln y ) = = n → ∞ lim ( 1 + n π ) n ln ( n sin n π ) n → ∞ lim n ln ( 1 + n π ) + ln [ ln ( n sin n π ) ]
Applying the standard limits, we get
ln ( ln y ) = = = = π + ln ( ln π ) ln ( e π ) + ln ln π ln [ ( e π ) ⋅ ln π ] ln [ ln ( π e π ) ]
Hence, ln ( ln y ) = ln [ ln ( π e π ) ] , or y = π e π . Hence, the limit is equal to π e π .